2019
DOI: 10.3390/ani9110963
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Body Measurements, Carcass and Some Internal Organs Characteristics of Pekin Ducks

Abstract: Simple SummaryThe protection and conservation of native poultry breeds, including ducks, is important for biological, cultural, emotional and scientific reasons. The objective of this study was to compare three lines of Pekin ducks for growth performance, body measurements, carcass and digestive system characteristics. The results showed significant differences between the tested lines of ducks in body weight and body measurements, as well as a small number of significant differences in carcass and digestive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
2
9
0
2
Order By: Relevance
“…In a crossbreeding study with Pekin, Deshi and Jinding ducks, the breast meat yield was found significantly higher (P<0.05) in (Pekin × Pekin) than that of (Pekin × Deshi) and (Pekin × Jinding) crossbreds (Ansary et al, 2008) and is consistent with the present study. Similar to the present findings, Kokoszyński et al (2019) found significant effects on preslaughter body weight, carcass weight, breast muscle yield, neck weight, liver weight and gizzard percentage among the three lines of Pekin ducks. Pekin derived crossbred ducks had better growth rate and meat yield characteristics like breast muscle yield, leg muscle yield and muscle yield in carcass at 8 weeks age (Padhi and Sahoo, 2012;Górska et al, 2014) and support the present results.…”
Section: Meat Yield Characteristicssupporting
confidence: 91%
“…In a crossbreeding study with Pekin, Deshi and Jinding ducks, the breast meat yield was found significantly higher (P<0.05) in (Pekin × Pekin) than that of (Pekin × Deshi) and (Pekin × Jinding) crossbreds (Ansary et al, 2008) and is consistent with the present study. Similar to the present findings, Kokoszyński et al (2019) found significant effects on preslaughter body weight, carcass weight, breast muscle yield, neck weight, liver weight and gizzard percentage among the three lines of Pekin ducks. Pekin derived crossbred ducks had better growth rate and meat yield characteristics like breast muscle yield, leg muscle yield and muscle yield in carcass at 8 weeks age (Padhi and Sahoo, 2012;Górska et al, 2014) and support the present results.…”
Section: Meat Yield Characteristicssupporting
confidence: 91%
“…These results were in line with the study of Oguntunji and Ayorinde (2014) that the body sizes of the Muscovy duck of the male Muscovy duck are more prominent than that of the female. Previous studies reported that weight, body length, body height, body circumference, neck length, and wing length in male Pekin ducks were greater than in females (Kokoszyński et al, 2019). This was due to the influence of the male hormone testosterone.…”
Section: Discussionmentioning
confidence: 84%
“…The strong relationship between bodyweight and the breast and thigh weights is due to the fact that in these parts of the carcass there is greater deposition of muscle tissue (Ogah, 2011). Other studies in chickens (Melo et al, 2003;Yang et al, 2006;Mendeş & Akkartal, 2009;Yakubu et al, 2009;Erensoy et al, 2020), ducks (Bochno et al, 2000;Kleczek et al, 2006;Kokoszyňski et al, 2019), and guinea fowl (Ogah, 2011) also reported high and significant correlations between bodyweight and body measurements with carcass characteristics and primal cut weights. This suggests that bodyweight and body measurements could be used as reliable predictors of carcass composition.…”
Section: Predictive Equations Of Carcass Characteristics and Primal C...mentioning
confidence: 93%